The Misconceptions of Students on Equations based on Their Arithmetic Knowledge - Lia Ardiansari; Didi Suryadi; Dadan Dasari (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
Many students have an operational view of the equals sign. This conception is seen as a misconceptions. This study aims to investigate the extent to which students have misconceptions about equality, where the equal sign is the focus. This research is a descriptive qualitative research with a case study approach. A total of 35 students in the city of Bandung became participants in this study. The results of the study reported that there were several misconceptions such as closing, using all numbers in the equation, string operations, and “pindah ruas”.